Smart Branding: Integration Of AI In The Marketing Strategy Of Bali MSME Cultural Products - Made Setini; Made Juliasa (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2026)
The development of Artificial Intelligence (AI) technology has provided a great opportunity for culture-based Micro, Small, and Medium Enterprises (MSMEs) to strengthen their marketing strategies in the digital era. This study aims to analyze the influence of AI Integration on marketing performance with smart branding as a mediating variable, as well as examine the role of cultural brand identity in strengthening the competitiveness of cultural MSME brands in Bali. Using an explanatory quantitative approach, data was collected through a survey of 150 cultural MSME actors who actively use digital media. The analysis was carried out using Partial Least Squares–Structural Equation Modeling (PLS-SEM) through the SmartPLS 4 application. The results of the study show that AI Integration has a significant positive effect on smart branding, which further improves cultural brand identity and marketing performance. These findings confirm that AI not only serves as an automation tool, but also as a strategic enabler in connecting local cultural values with the needs of modern markets. Furthermore, smart branding has proven to be a bridge between technological capabilities and the preservation of cultural values, strengthening brand image and customer loyalty. Theoretically, this study expands the application of Dynamic Capability Theory by affirming AI as a new form of dynamic capability in culture-based brand management. Practically, the results provide guidance for Balinese cultural MSMEs in optimizing AI to create an adaptive, authentic, and sustainable branding strategy.